Escaping the "virtual promenade" – new trends in use of social networks by members of generation "z" - Levak, Tomislav (Array, 2018)
The aim of this paper is to determine whether the younger population in Croatia is following the dominant world trends in the use of social networks as extremely widespread communication platforms. Namely, although the Facebook community currently consists of as many as two billion users and is still convincingly the most popular social network in the world, it has already been noted that members of the so-called generation Z (people born after 1995) across the world are increasingly abandoning or minorizing Facebook and turning to other social networks. To this end, the authors used the comparative method to investigate the use of several contemporary social networks and current trends in the world and Croatia, using the necessary theoretical framework. Also, during May of 2017, the authors conducted a research into online habits and attitudes on social networks – which has not yet been done in Croatia, in the authors' knowledge – by means of an online survey among secondary school students, members of generation Z, in several major and smaller Croatian cities: Zagreb, Osijek, Krk and Korčula. The results of the research confirmed the initial hypotheses of the authors: young people are increasingly leaving Facebook as a “virtual promenade”, largely because older generations began using it, including their parents; they are mostly turning to social networks that offer a prevalence of photographs over text, primarily Instagram and Snapchat. In addition, no significant differences were found between members of generation Z in larger urban areas on the continent and smaller urban areas on the Adriatic islands, when it comes to their preferences.